Utro . Utro . Morning . Утро - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Establishment of the State Council of Defense; plenary meeting of the Children's Fund. Series description: A morning news program, broadcasted since 1986, and including several news and entertainment programs. The program had several names. At first it was called "60 Minutes," in 1988 it became known as "90 minutes," and later in 1989 was changed to "120 minutes". The first major hosts were Oleg Dobrodeyev, Boris Kostenko, Evgenii Kiselyov, Tatiana Mitkova, Mikhail Osokin, Sergei Alekseev, Sergei Dorenko, and Irina Mishina. After 1989 the program became known as "Morning," from April 1995 "TV Morning," and since 1997 "Good Morning." Создание государственного совета обороны, проведение пленума детского фонда. Описание серии: Программа включает в себя публицистические и развлекательные эпизоды, а также новости. Сначала программа называлась "60 минут." С 1988 она стала называться "90 минут," позже, до 1989 года - "120 минут." Первыми ведущими передачи, до появления программы "Телевизионная служба новостей" были Олег Добродеев, Борис Костенко, Евгений Киселёв, Татьяна Миткова, Михаил Осокин, Сергей Алексеев, Сергей Доренко, Ирина Мишина. С 1989 года программа стала называться "Утро," с 1 апреля 1995 года - "Телеутро," с 1997 года - "Доброе утро."